Urban Elites, Energy, and Smoke Policy in Montreal during the Interwar Period - Temby, Owen; MacFadyen, Joshua (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 2016)
During the late 1920s and early 1930s, Montreal’s air was blackened by smoke from coal-burning homes, factories, and the locomotives and lake freighters connecting its growing economy to the rest of Canada. Lacking regulatory tools suited to the task of abating this nuisance, the municipal government passed the country’s first modern smoke bylaw, consisting of an objective emissions standard, a smoke control bureau, and requirements for the installation and utilization of technology to lessen emissions. In providing an account of the process through which Montreal’s smoke nuisance was addressed, this article describes the role of the city’s most influential local growth coalition, the Montreal Board of Trade, in introducing the issue on the city’s policy agenda, participating in the formulation of a policy response, and monitoring the implementation of the resulting bylaw. The Board of Trade sought a resolution to the problem because it damaged the city’s reputation and business climate. Consistent with other documented examples of smoke abatement in large urban areas, the response promoted by this elite growth coalition consisted largely of technology-based measures that managed the problem while eschewing recourse to measures that would dampen economic activity.